EFFECTIVENESS OF SEMBALUN ARABIC COFFEE (Coffea arabica) ACTIVE COMPOUNDS AS AN ALTERNATIVE FOR REDUCING OBESITY - Ningsih, Suci Apriliya; Wahid, Abdul Rahman; Syafutri, Yemi Agustin; Nurfatiha, Tita; Safwan, Safwan; Wardan, Alvi Kusuma (Universitas Muhammadiyah Magelang, 2024)
Obesity has become a global public health and nutrition problem, both in developed and developing countries. Based on the latest Riskesdas data in 2018, the prevalence of obesity in adults aged >18 years is still increasing, at 21.8%. Arabica coffee (Coffea Arabica) has active compounds such as caffeine, alkaloids, flavonoids, saponins, and tannins that can be used to reduce the risk of causing obesity. This study aims to determine the decrease in obesity index of wistar male white rats given ethanol extract of arabica coffee beans for 24 days in obese model rats induced with high fat diet for 50 days. Extraction was carried out on Arabica coffee beans using 96% ethanol solvent for 3x24 hours by maceration method. The treatment was carried out with extract doses of 200 (D1), 400 (D2), and 600 (D3) mg/kg BW for 24 days. Experimental animals were divided into 5 groups, namely negative control given 1% CMC, positive control given orlistat 30 mg/kg BW, control group given ethanol extract of Arabica coffee beans at a dose of 200 (D1) mg/kg BW, 400 (D2) mg/kg BW, and 600 (D3) mg/kg BW. Obesity parameters were measured by Lee index and fat index. Arabica coffee extract (ACE) at a dose of D1 mg/kg BW showed a decrease in body weight of 47.88%, higher than the dose of D2 by (23.49%) and D3 by (14.00%). Caffeine contained in Arabica coffee beans (Coffea arabica) shows potential as an obesity inhibiting agent. The effective dose of ethanol extract from Arabica coffee beans (Coffea arabica) which has the effect of lowering the obesity index is in the D2 group.